Origins of political order - Fukuyama, Francis (London, 2011)
This book has two origins. The first arose when my mentor, Samuel Hun tington of Harvard University, asked me to write a foreword to a reprint edition of his 1968 classic, Political Order in Changing Societies. Hunting ton's work represented one of the last efforts to write a broad study of po litical development and was one I assigned frequently in my own teaching It established many key ideas in comparative politics, including a theory of political decay, the concept of authoritarian modernization, and the notion that political development was a phenomenon separate from other aspects of modernization.
Keywords: Politics-Primate ancestors